Electropolymerization reaction-driven 2, 6-naphthalenediamine monomers to a multilayered sheet structure for ultralong cycling aqueous zinc-ion batteries. (14th September 2022) - Xie, Yishun; Su, Weilong; Hu, Qiong; Lai, Feiyan; Yan, Zhixiong; Huang, Guobao; Lu, Shaorong; Zhang, Xiaohui
Abstract : 2, 6-NAPD monomers are used as cathode materials and electropolymerized into multilayered sheets after ultralong cycling in aqueous zinc-ion batteries. Abstract : Organic materials are attractive for energy storage due to their stable structure, environment-friendly nature and sustainability. In this work, a 2, 6-naphthalenediamine (2, 6-NAPD) monomer was first used as the cathode material in aqueous zinc-ion batteries (ZIBs). Electropolymerization by the initial electrode reaction eliminates energy consumption in the beforehand polymerization process and provides a simple method to synthesize polymeric cathode materials. The possible bond connection mode of 2, 6-NAPD monomers was proposed using the 13 C-nuclear magnetic resonance and Fourier-transform infrared spectra. Scanning electron microscopy shows that the irregular 2, 6-NAPD monomers form multilayered sheets after long-term cycling. The 2, 6-NAPD electrode delivers a specific capacity of 133.1 mA h g −1 at 0.05 A g −1 and excellent cycling stability with a capacity retention of 76.5% over 8000 cycles.